(untitled) (Research, Society and Development, 2021)
Humanization is essential to overcome the barriers of different types of relationship for human care. In the context of health services, this matter has been heavily emphasized in the hospital environment, but not too much has been seen in practice. The objective of this work was to identify the knowledge of humanized care by a multidisciplinary team in a coronary ICU, focusing in aspects related to ambience, the right to have a companion during the hospitalization and routines performed in the ICU. The study was conducted with an exploratory qualitative approach, carried on in the Coronary ICU of a public hospital in the city of Fortaleza, state of Ceará. Data was collected through a sociodemographic/professional questionnaire and a semi structure interview, based on Minayo. Three doctors, five nurses, three physiotherapists and five nursing technicians participated. Six categories were identified: Humanization is learned in practice; Empathy with everyone; Routine mechanizes professional action; Companion hinders lack of preparation; Quiet and peaceful environment; and Elements for the qualification of workers. The study revealed that the humanization of healthcare in ICUs is essential for all health professionals in the hospital dynamics. The health professionals realized that it is necessary to combine available technology with empathy and care in the therapeutic interpersonal relationship so that safe and ethical care for critical patients can be promoted. In addition, it was highlighted that the companion offers support and safety for the patient, since its presence is being important, as well as the need for continuous improvement of the team as a basic tool for the practice of humanization.